Situação vacinal de crianças atendidas em uma unidade de saúde na cidade de Porto Velho - CANIZARES, Vivian Susi de Assis (Universidade Federal do Pará, 2013)
This study analysed the vaccionation of 173 children under 2 years old attended at the ambulatory of Policlínica Hamilton Raulino Gondin, situated in Porto Velho. The data were collected in the period frem May to September of 2001 and it was made by filling in a model form. The children's vaccination cards were analysed for previus annotation. The social-economics status and culture situation of the children's families were investigated too. The vaccination delays found were 6,4% for yelow fever vaccine, 5,8% for first and second doses of measles vaccine and for third dose against Hib disease. The most relevant cause for vaccination retard was the mother's lack of information. The maternal age detected was between 19 and 25 years old. 63,0% of the children's guardians had an incomplete elementary schooll education. The average family income was between 1 and 2 minimum salaries.